PENGARUH VARIABEL FINANCIAL STABILITY, EXTERNAL ‎PRESSURE ‎TERHADAP FRAUD LAPORAN KEUANGAN DENGAN ‎PENERAPAN ‎PSAK 116 SEBAGAI VARIABEL MODERASI - Fatimah, Siti; Kusuma, Indra Cahya; Didi, Didi (Komunitas Manajemen Kompetitif, 2024)
The purpose of this study was to analyze how financial stability and external pressures affect ‎the fraud of financial statements with PSAK 116 as a moderation variable. The population in ‎the study included comp anies listed on the Indonesia Stock Exchange, which is part of the ‎lq45 index, from 2014 to 2023, with a total of 72 companies. The samples were taken by ‎purposive sampling method, which produced 6 companies during the 10-year period. Data ‎analysis was conducted using descriptive statistical analysis methods and inferential statistics ‎using Eviews 12. The results showed that partial financial stability and external pressure have ‎a positive effect on financial statement fraud. In addition, PSAK 116 is able to strengthen the ‎influence of financial stability on financial statement fraud, but weaken the influence of external ‎pressure on financial statement fraud. The results of the study concluded that increased ‎financial targets associated with increased levels of fraud in financial reporting. In addition, ‎institutional ownership can weaken the influence of financial targets on fraud in the company's ‎financial statements.‎ Keywords: Financial Stability, External Pressure, PSAK 116, Financial Statement Fraud